2021
DOI: 10.4314/gmj.v55i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of extended-spectrum β-lactamase in clinical Escherichia coli isolates at Ho Teaching Hospital in Ghana.

Abstract: Objective: This study determined the occurrence and distribution of Extended Spectrum β-Lactamase (ESBL) genotypes of E. coli isolates in Ho Teaching Hospital, Ghana.Design: A cross-sectional study.Setting: A single centre study was conducted at Ho Teaching Hospital of Ghana.Participants: Patients who visited Ho Teaching Hospital Laboratory with the request for culture and susceptibility testing.Main outcome measure: Escherichia coli were isolated, and Extended-Spectrum β-Lactamase genes were detected.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Elsewhere, ESBL prevalence of 50% from northwestern Nigeria [ 12 ], 42% in Lagos, Nigeria [ 36 ], South Africa (36.1%) [ 13 ], Tunisia (38.5%) [ 14 ], and Tanzania (15%) [ 33 ] was reported. The ESBL genotypes obtained in Ho Municipality among the pregnant women were similar to those obtained in Accra [ 9 ] and a much earlier study that recorded an ESBL prevalence of 41.5% at the Ho Teaching Hospital [ 11 ]. In the present study, the prevalence of Bla TEM was 45 (71.4%), Bla CTX-M 42 (66.7%), and Bla SHV 2 (3.2%).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Elsewhere, ESBL prevalence of 50% from northwestern Nigeria [ 12 ], 42% in Lagos, Nigeria [ 36 ], South Africa (36.1%) [ 13 ], Tunisia (38.5%) [ 14 ], and Tanzania (15%) [ 33 ] was reported. The ESBL genotypes obtained in Ho Municipality among the pregnant women were similar to those obtained in Accra [ 9 ] and a much earlier study that recorded an ESBL prevalence of 41.5% at the Ho Teaching Hospital [ 11 ]. In the present study, the prevalence of Bla TEM was 45 (71.4%), Bla CTX-M 42 (66.7%), and Bla SHV 2 (3.2%).…”
Section: Discussionsupporting
confidence: 80%
“…This means that there is high prevalence of community-acquired ESBL circulating in the Ho Municipality. The high ESBL prevalence observed in this study holds the potential to result in significant treatment failure and the narrowing of the antibiotic spectrum due to its destructive effect on cephalosporins [ 11 ]. Meanwhile, when we consider the growing level of self-medication in our communities without prior laboratory investigation coupled with the difficulty in detecting ESBLs and the inconsistencies in reporting ESBLs within the community, we fear a surge in antibiotic resistance moving forward and the consequences among pregnant women may be dire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Deku and colleagues investigated the burden of bacteria specifically resistant to four fluoroquinolones at the Ho Teaching Hospital in Ghana. They found that 90 out of 135 Escherichia coli isolates were resistant to at least one of the four fluoroquinolone drugs investigated [39].…”
Section: How Prokaryotes Fight Back By Developing Resistancementioning
confidence: 99%
“…In particular, in certain geographical markets, for example in some certain developing countries, infections caused by E. coli diarrheal have been transferred through human contacts, like enteroaggregative E. coli (EAggEC), endemic [8].Furthermore, the treatment with human manures is frequentlyunusable or levellacking. Therefore, it principals to a wide spreading of these pathogens in the surrounding environment and then they might have contact with Shiga toxin-producing E. coli (STEC).We examined the presence of pathogenic E. coli, mainly entropic ones, in specimens isolated from infant clinical specimens [9].Molecular characterization has manifested high degree of diversity among virulence factors in different strains of atypical EPEC [10].The pathogenicity of degree of extraintestinal E. coli isolates is dependent on the existence of fimbriae adhesions (fimA, sfa/foc, and yfcV) which are documented as very important factors that are responsible for the related adherence [11].…”
Section: Introductionmentioning
confidence: 99%